Pan-Genome Analysis of Laribacter hongkongensis: Virulence Gene Profiles, Carbohydrate-Active Enzyme Prediction, and Antimicrobial Resistance Characterization - Yuan, Pei-Bo; Zhan, Yi; Zhu, Jia-Hui; Ling, Jia-Hui; Chen, En-Zhong; Liu, Wan-Ting; Wang, Lin-Jing; Zhong, Yu-Xia; Chen, Ding-Qiang (Frontiers in Microbiology, 2022)
Laribacter hongkongensis is a new emerging foodborne pathogen that causes community-acquired gastroenteritis and traveler’s diarrhea. However, the genetic features of L. hongkongensis have not yet been properly understood. A total of 45 aquatic animal-associated L. hongkongensis strains isolated from intestinal specimens of frogs and grass carps were subjected to whole-genome sequencing (WGS), along with the genome data of 4 reported human clinical strains, the analysis of virulence genes, carbohydrate-active enzymes, and antimicrobial resistance (AMR) determinants were carried out for comprehensively understanding of this new foodborne pathogen. Human clinical strains were genetically more related to some strains from frogs inferred from phylogenetic trees. The distribution of virulence genes and carbohydrate-active enzymes exhibited different patterns among strains of different sources, reflecting their adaption to different host environments and indicating different potentials to infect humans. Thirty-two AMR genes were detected, susceptibility to 18 clinical used antibiotics including aminoglycoside, chloramphenicol, trimethoprim, and sulfa was checked to evaluate the availability of clinical medicines. Resistance to Rifampicin, Cefazolin, ceftazidime, Ampicillin, and ceftriaxone is prevalent in most strains, resistance to tetracycline, trimethoprim-sulfamethoxazole, ciprofloxacin, and levofloxacin are aggregated in nearly half of frog-derived strains, suggesting that drug resistance of frog-derived strains is more serious, and clinical treatment for L. hongkongensis infection should be more cautious.